(untitled) (Global Journal of Medical Research, 2015)
The prevalence rate of asymptomatic UTI among students of a community tertiary institution based in Evbuobanosa near Benin City, Nigeria was the focus of this work. A total of 390 freshly voided midstream urine samples collected into sterile plastic screw capped universal containers containing boric acid as preservative from students aged between 15 -30 years were used for the study. Samples were screened for significant bacteriuria and puscells (neutrophil) counts. All positive samples with pyuria were aseptically cultured by standard methods on sterile Cystine Lactose Electrolyte Deficient (CLED) agar, MacConkey agar and Sabouraud Dextrose agar plates and incubated appropriately. Antibiotic susceptibility testing was done on isolated and identified uropathogens by Kirby -Bauer agar diffusion disc method. While 231(59.2%) samples yielded bacterial growth, 159(40.8%) yielded no growth.